Response parameters for characterization of infiltration - Rahardjo, Harianto (2011)
Rainwater infiltration is of particular interest with respect to slope stability hazard management. The process of rainfall infiltration into unsaturated soil is complex due to the number of soil parameters involved and the random nature of moisture flux boundary conditions. In this paper, the effect of rainfall intensity on infiltration is investigated through the use of finite element seepage modeling for a 5 m high soil column subjected to various rainfall intensities. The numerical modeling study identified three response parameters that can be used to describe one-dimensional infiltration into an unsaturated soil. The response parameters are the depth of wetting front, the matric suction reduction depth, and the sectional infiltration rate. The practical application of the rainfall response parameters in slope stability analysis is illustrated.